A persistência do aviamento : colonialismo e história Indígena no noroeste Amazônico - Meira, Márcio (Coleção Aracy Lopes da Silva. Estudos em antropologia social., 2018)
Anthropologist Márcio Meira analyzes the process of colonization of the Amazon Northwest region since its genesis, centered on the so-called "Aviamiento" system, one of the structuring factors of the sociology of this region. The a Debt-Servitude System ("Aviamiento") is characterized by asymmetric barter-to-credit trade, establishing a debt relationship and a hierarchical network of domination between bosses and customers. Indigenous people impacted by the persistence of this debt slavery (or bonded labour), understood as a colonial condition, have been able to work for a long time on the margins of the regime of violence, renewing their old fluid and open social system. In an interdisciplinary methodological approach to the colonial process, this work establishes a dialogue between history and memory.